GAMBARAN PENGETAHUAN FAKTOR RESIKO PENYAKIT PARU OBSTRUKTIF KRONIK PADA PASIEN PPOK - Nanda Rizky Agustin; Yosep Rohyadi; Sansri Diah KD; Yati Tursini (Politeknik Kesehatan Kemenkes Bandung, 2020)
This research is motivated by the incidence of COPD in Indonesia as much as 4.8 million in 2011. The incidence of COPD in West Java reached 3,941 people in 2012 while in Bandung around 1,081 people in 2017. COPD is a disease characterized by air flow obstruction in airway that is not completely reversible. These air flow barriers are progressive and are associated with the inflammatory response of the lung to toxic or dangerous particles or gases. The causes, signs of symptoms, complications, and prevention of complications need to be known by COPD patients to prevent the occurrence of severity, one of the factors that influence is the description of COPD patient knowledge. This study aims to determine the knowledge of COPD risk factors in COPD patients. The research method use a study literature review. Researchers examined 3 articles related to the description of COPD knowledge. The study came from Fadhil in 2013, Adelima in 2019, and Maria in 2012. The results showed that the factors often found in influencing knowledge were education and experience factors. In addition, there are still many COPD patients who don’t know very well about these COPD risk factors, this affects the lifestyle and treatment compliance. It’s expected that surgical medical nurses can provide health education to COPD patients about the importance of knowing the risk factors for COPD to prevent severity. Key words: The knowledge description of COPD